DEVELOPMENT OF SOLAR ENERGY HARVESTER FOR INTERNET OF THINGS - AHMAD PUAT, NADHIRA NATASYA (2017)
Internet of Things (IoT) which has now received worldwide demand is used to provide real time data monitoring for application via the Internet. However, a remote and portable IoT needs to have a good power source in supplying the energy required by the sensor node. Hence, solar energy harvester is the most preferred option in supplying the power required as it has the maximum power density generated compared to the other energy harvesters. This project emphasizes on having a good and suitable power management scheme and energy storage solution of solar energy harvester for IoT. Owing to this, the solar energy harvester system is designed to have a Battery Charger with Maximum Power Point Tracking (MPPT) application to ensure it can extract the maximum amount energy generated by the solar module. On the other hand, use of Nickel-Metal Hydride (NiMH) rechargeable batteries as energy storage solution will also ensure a better efficiency of the solar energy harvester system so that there will be no energy wasted. Thus, this ensures the solar energy harvester system to have a high efficiency as the result of good power management scheme and suitable energy storage solution that has been developed in this project. From this project, a scalable and customizable solar energy harvester system can be developed for the application of remote IoT.